Phenotypic evolution of an Atlantic Forest passerine (Xiphorhynchus fuscus): biogeographic and systematic implications - Cabanne, Gustavo Sebastián (2014)
We studied the phenotypic variation of the Atlantic Forest passerine Xiphorhynchus fuscus (Aves: Dendrocolaptidae) with the broad aim of addressing whether the history and type of forest affected the evolution of endemic taxa. We also tested whether the different subspecies and genetic lineages of X. fuscus could be considered full species. We collected plumage and body size measurements and, in combination with genetic data, used multivariate tests to evaluate the working hypotheses. Our results, combined with previous biogeographic analyses, indicate that vicariant events have been important determinants in the evolution of phenotypic characters of X. fuscus, once genetic isolation was complete. Our analysis also suggests that forest heterogeneity and ecotones are important factors in the early evolution of Atlantic Forest taxa, perhaps via divergent selection. Forest instability during the Pleistocene was critical in the evolution of phenotypic traits. We confirm that the subspecies atlanticus should be considered a full species. Other lineages or populations are also phenotypically differentiated but we do not suggest considering them as full species. They share high levels of gene flow and are part of a continuous latitudinal cline of phenotypic variation. Our study suggests that not all the historic events in the Atlantic Forest that affected the evolution of genetic lineages also influenced the evolution of phenotypic characters in the same direction and intensity. Undoubtedly, natural selection played a major role in the evolution of Atlantic Forest organisms.